폐구인상채득법을 이용한 임플란트 인상채득 증례 - 김소연(So-Yeun Kim); 김주현(Joo-Hyeun Kim); 정경화(Kyoung-Hwa Jung); 전혜미(Hye-Mi Jeon); 강은숙(Eun-Sook Kang); 윤미정(Mi-Jung Yun) (Journal of dental rehabilitation and applied science, 2017)
Closed mouth impression technique by using bite tray is preferred for single tooth impression taking. However, for implant impression taking, open mouth impression technique by using single arch tray is generally used whether it is for single implant or multiple implant. Closed mouth impression technique by using bite tray can save time and materials. It also decreases the chance of error occurrence when a model is mounted on an articulator. In this case report, we tried to show a satisfying result of fabricating single implant fixed prosthodontics after bite tray impression taking by using two different copings for closed mouth impression. 단일 치아의 인상채득을 위해서는 바이트 트레이를 이용한 폐구인상법이 선호된다. 그러나 임플란트 인상채득을 위해서는 단일치와 다수치 구분 없이 편악 트레이를 이용한 개구인상법이 주로 사용되고 있다. 바이트 트레이를 이용하는 폐구인상법은 시간이 절약되고 재료가 적게 들며, 모형의 교합기 부착 시 상하악 악간 위치 관계 오차 발생 확률이 적다. 본 증례에서는 2 가지 종류의 폐구인상용 코핑을 이용해 바이트 트레이로 인상채득 후 단일 임플란트 고정성 보철물을 제작함에 있어 만족할 만한 결과를 얻어 보고하고자 한다.